Seroprevalence and newly isolated strains of LT-Ag gene (MMGHA2 and MM GHA5) of BK Polyomavirus in A Sample of Iraqi renal transplant recipients (Journal of Pharmaceutical Negative Results, 2022)
Background: BK virus (BKV) opportunistic viral infection causes nephropathy and allograft loss in renal transplant recipients (RTRs).Aims: Investigating BKV seropositivity, viremia rate and renal function were the primary goals of this study, in addition to the molecular study of the Iraqi BKV strains (LT antigen gene).Settings and Design: Case-control study.material and methods: Serum and plasma specimens were collected from 106 RTR and 100 non-RTR. Serum samples were analyzed for anti-BK IgG antibodies by BK-IgG ELISA kit. Plasma samples were used for detection of large tumor (LT-Ag) gene region of BKV by RT-PCR technique and then sequenced by Sanger's method.Statistical analysis: frequencies, percentages, and Chi square-test by SPSS v.28Results: The Study showed that 114 (55.3%) have a positive result for BK-IgG, so there was no significant difference between seropositivity of BKV IgG antibody among the studied groups, p =0.191. On the other hand, a total of 206 subjects, 31 (15.0%) had positive viremia and 175 (85.0%) were negative. Renal function showed highly significant differences (p ≤0.000) between seropositive and negative RTR patients. 2 sequences of Iraqi local strains were deposited in the GenBank with the accession numbers LC718551.1 and LC718552.1Conclusions: The viremic state of BKV in RTR has similarly no impact on renal function. While the highly significant association between seropositivity of BK-IgG with high levels of serum creatinine. New strains of BKV were found in the Iraqi RTR patients with 98% similarity with the reference gene.